Do Green Practices in the Hotel Attract Customer to Revisit? A Study in a Green Hotel in Surakarta - Astuti, Septin Puji; Ermawati, Yuni (Management Analysis Journal, 2020)
The Ministry of Environment of the Republic of Indonesia encourages sustainable tourism and hospitality industry to achieve green hotel and green tourism in 2020. Rumah Turi as one of hotel destinations in the middle of Surakarta has provided green practice and facilities in the hotel. This study intends to investigate the determinant factors of revisit intention to Rumah Turi. This study is conducted to hotel customers who have visited Rumah Turi. Sample of this study is 131 customers of Rumah Turi from various cities in Indonesia. Five independent variables, i.e. green practice, service quality, facility, price and location, are applied in this study to be identified of their influence to revisit intention. By implementing linear multiple regression analysis, it is found that this study unable to make evidence that service quality and price influence customer to have the intention to revisit Rumah Turi. However, by using moderated multiple regression analysis, this study has proven three models of the determinant factors of revisit intention. The first model (Model 3) is, the moderator of service quality to facility and the moderator of price to location, in addition to green practice have significantly influenced revisit intention. Second model is Model 4, where green service and service quality are the moderators of facility and price as the moderator of location have significantly influenced to revisit intention. Third model is Model 5, where service quality, price and green practice are the moderators of facility altogether with location have significantly influenced revisit intention.